(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The article deals with the issues of diagnosing the technical condition of aviation equipment, the goals and objectives of technical diagnostics, non-destructive methods for monitoring aviation equipment.